Comparison of square and circular isolated pad foundations in cohesionless soils - Komolafe, O. O.; Balogun, I. O.; Abiodun, Y. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
One of the most commonly used pad foundation types is the square footing, however, there is a necessity to compare its performance and economy with the circular pad foundation which is not often considered. This study focuses on the suitability of the square versus circular isolated pad foundation types in cohesionless soils, from a geotechnical, structural, and construction cost perspective. The square and circular pad foundation types were subjected to three (3) cases, which were: when the foundation footings have equal width or diameter (Case 1), when the foundation footings have an equal axial load capacity (Case 2), and when the foundation footings are restricted to a defined net allowable bearing capacity (Case 3). The factors evaluated in each of these cases were bearing capacity, immediate settlement, structural design, and construction cost. Additionally, a model for estimating the construction cost of reinforced concrete was proposed in this study, and it was used to estimate the construction cost of the reinforced concrete isolated pad foundation types. The results of this research work show that overall, the square isolated pad foundation type will be the better selection for most design and construction considerations,